2017
DOI: 10.3389/fimmu.2017.00103
|View full text |Cite
|
Sign up to set email alerts
|

CD161+ Tconv and CD161+ Treg Share a Transcriptional and Functional Phenotype despite Limited Overlap in TCRβ Repertoire

Abstract: Human regulatory T cells (Treg) are important in immune regulation, but can also show plasticity in specific settings. CD161 is a lectin-like receptor and its expression identifies an effector-like Treg population. Here, we determined how CD161+ Treg relate to CD161+ conventional T cells (Tconv). Transcriptional profiling identified a shared transcriptional signature between CD161+ Tconv and CD161+ Treg, which is associated with T helper (Th)1 and Th17 cells, and tissue homing, including high expression of gut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 71 publications
(76 reference statements)
3
25
0
Order By: Relevance
“…This can be appreciated in the clear clustering by cell type in CDR3 amino acid-based multidimensional scaling and the heatmap of EAE clonotypes, which identifies distinct clonotype usage in Tcon and Treg. These observations are in line with previous work, showing that Tcon and Treg strongly differ in clonal composition (23,41), indicating that they are recruited from different clonal pools during thymic development (42) and that trans-differentiation between both subtypes is limited (23).…”
Section: Discussionsupporting
confidence: 92%
“…This can be appreciated in the clear clustering by cell type in CDR3 amino acid-based multidimensional scaling and the heatmap of EAE clonotypes, which identifies distinct clonotype usage in Tcon and Treg. These observations are in line with previous work, showing that Tcon and Treg strongly differ in clonal composition (23,41), indicating that they are recruited from different clonal pools during thymic development (42) and that trans-differentiation between both subtypes is limited (23).…”
Section: Discussionsupporting
confidence: 92%
“…Given this observation, it will be intriguing for future studies to interrogate relationships between the TCR repertoires of Th17 and Treg cells within the joints of O-JIA patients, in order to establish whether the reciprocal relationship arises from discrete clones, or whether Th17/Treg plasticity is an important mechanism. For instance hybrid IL-17A + FOXP3 + Treg, identified by expression of CD161, are significantly enriched at the site of inflammation ( 37 , 38 ), and repertoire overlap between CD161 + Treg and Tconv as a proportion of CD161 + SF Treg was in the region of 20–30% ( 38 ), suggesting plasticity of T-cell responses within the joint. In summary, what these papers clearly show is that the joint environment is highly dynamic, and that snapshot in time analyses may obscure observations that may be accounted for by cellular and molecular dynamics.…”
Section: Dynamics and Clonal Relationships Between Foxp3 + mentioning
confidence: 99%
“…Furthermore, several other studies demonstrated that DCs produced RA, which mediated CCR9 expression in T cells ( 25 ) and induced interleukin 10 (IL-10) expression in α4β7 + CCR9 + T cells ( 26 ). T cells were also mediated by RA directly via the RA receptor, which upregulated CCR9 expression ( 27 , 28 ). Therefore, decreased expression of the RA receptor was associated with a reduction in CCR9 expression and an attenuation of graft-versus-host disease ( 29 ).…”
Section: Chemokine Receptor 9 In Leukocytesmentioning
confidence: 99%